Fine microstructure of processed chitosan nanofibril networks preserving directional packing and high molecular weight. (20th October 2015) - Osorio-Madrazo, Anayancy; David, Laurent; Peniche-Covas, Carlos; Rochas, Cyrille; Putaux, Jean-Luc; Trombotto, Stéphane; Alcouffe, Pierre; Domard, Alain
Highlights: Mild hydrolysis is an effective method to produce highly crystalline chitosan nanofibril networks with potential use as nanoreinforcement. Chitosan nanofibrillar networks were obtained and the native directional packing was preserved in the crystalline phase. The nanostructure of chitosan materials was characterized in detail by complementary synchrotron SAXS and WAXS, TEM and electron diffraction. Indexation and quantification of distinct experimental X-ray diffraction patterns of chitosan could be performed on samples consisting of anhydrous; hydrated; or a mixture of both allomorphs in the crystalline phase. Abstract: Crystalline chitosan nanofibril networks were prepared, preserving the native structural packing and the polymer high molecular weight. The fine microstructure of the nanomaterial, obtained by mild hydrolysis of chitosan (CHI), was characterized by using synchrotron small- and wide-angle X-ray scattering (SAXS and WAXS), transmission electron microscopy (TEM) and electron diffraction. Hydrolysis of chitosan yielded a network of crystalline nanofibrils, containing both allomorphs of chitosan: hydrated and anhydrous. The comparison of WAXS data in transmission and reflection mode revealed the preferential orientation of the CHI crystals when subjected to mechanical compression constrains. The results are in agreement with the existence of a network nanostructure containing fiber-like crystals with the principal axis parallel to the polymer chain axis. The evolution of the CHI allomorphic composition with temperature was studied to further elucidate the mechanism of structural transitions occurring during CHI nanofibril network processing.